Modeling of information support to optimize logistics tasks in transport sector using a programmable container transformer simulator - A. A. Korotkii; D. A. Yakovleva; A. A. Maslennikov; I. V. Golovko (Advanced Engineering Research)
Introduction. The structure of the transport logistics system for the transportation of container transformers in an urbanized environment to optimize production costs with elements of intelligent urban mobility, as well as the simulation software for modeling and testing the developed system, are described. The basic principles of the interaction between elements of the system are presented through the behavioral modeling of containers and carriers.Software is created to simulate the operation of the logistics infrastructure for transformer containers using wireless technology and the Internet of Things; and services for the rapid information exchange between participants (objects and subjects) of this process are implemented. Materials and Methods. A general method of organizing a network with a web server and a mobile client, as well as the basic principle of interaction between the server and the client, is described. The basics of developing a simulator designed to simulate all possible states of a container transformer are specified.Results. A common system architecture and a simulator are created for the software debugging and testing under the organization of a single space to monitor and optimize cargo transportation using “smart” container transformers while providing transport services to the population and legal entities in an urban environment.Discussion and Conclusions. The developed simulator as part of the information system provides speeding up the creation, debugging and testing of the software for solving logistics problems in the transport sector.